Desenvolvimento de catalisadores bifuncionais ZnFe2O4/Nb2O5 para produção sustentável de biodiesel via fotocatálise heterogênea - Maroli Neto, Alberto Jose (2025)
The growth of the world population, together with the constant development of society, makes the use of fuels increasingly necessary. Biodiesel emerges as a renewable fuel that can be obtained from low added value raw materials, but this fuel is still little used compared to petrodiesel, as the synthesis processes present low yields, environmental problems with waste generation and demand a lot of energy. The need for more efficient and environmentally friendly processes makes the bifunctional photocatalytic-acid process a promising solution. The use of an acid catalyst together with a semiconductor sensitive to visible light can significantly improve the biodiesel production process. In this work, bifunctional zinc ferrite/niobium pentoxide (ZnFe2O4/Nb2O5) composite catalysts were developed by the hydrothermal coprecipitation method in different mass ratios between the compounds (100:0, 75:25, 50:50, 25:75 and 0:100%) niobium pentoxide and zinc ferrite, respectively. The catalysts were characterized by X-ray Diffractometry (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Nitrogen Physisorption and Energy Dispersive X-ray Scanning Electron Microscopy (SEM-EDS). The catalysts presented ZnFe2O4 and Nb2O5 as the majority phases. Vibrations consistent with the Nb-O, Fe-O and Zn-O bonds were verified, indicating the majority presence of the desired materials in the catalysts. The materials presented high surface areas, ranging from 108 to 166 m2 g-1. The catalysts were subsequently used in the esterification reaction of oleic acid with methanol in order to convert it into methyl oleate (biodiesel). In this context, 12 tests were performed in total, 6 with and 6 without the presence of radiation emitted by LEDs. The test using the catalyst composed of pure ZnFe2O4 in the presence of radiation obtained the best result, converting 58.5% of the acid into biodiesel. In the absence of radiation, the best conversion result (24.7%) was achieved by Nb2O5. These results show that the monofunctional mechanisms (acid catalysis and heterogeneous photocatalysis) prevailed over a bifunctional mechanism.